2011
DOI: 10.1007/s11581-011-0532-8
|View full text |Cite
|
Sign up to set email alerts
|

Point defect diagrams for pure and doped cobalt oxide $$ {\hbox{C}}{{\hbox{o}}_{{{1} - }}}_{\delta }{\hbox{O}} $$ in the temperature range of 1,173–1,673 K (I)

Abstract: The point defect diagram in non-stoichiometric cobalt oxide Co 1Àd O, pure and doped with M 3+ and M + metal ions, taking into consideration all of the types of defects in the cation sublattice are presented in this work. A new method was used for the calculations of the diagrams. This method is based on the derived relations between the standard Gibbs energies of formation of cobalt vacancies and the intrinsic ionic and electronic defects; it also uses the experimental values of the deviation from the stoichi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…The work (Stokłosa, 2011a) also demonstrated that the standard Gibbs energy of the formation of vacancies…”
Section: δYmentioning
confidence: 93%
See 4 more Smart Citations
“…The work (Stokłosa, 2011a) also demonstrated that the standard Gibbs energy of the formation of vacancies…”
Section: δYmentioning
confidence: 93%
“…Due to a low concentration of defects, the concentrations of defect complexes and defect clusters will also be low. It could be demonstrated very clearly that near the stoichiometric composition (δ0) the changes of the concentrations of the defects are infinitesimally small, yet are of the same order of magnitude (Stokłosa, 2011a). This is why the changes of the concentrations of defects (mole fractions) in Eqs.…”
Section: Standard Gibbs Energy Of the Formation Of Defects In An Oxidmentioning
confidence: 97%
See 3 more Smart Citations